INTEGRATION OF INFORMATION TECHNOLOGY INTO THE CURRICULUM OF THE BIOLOGY DEPARTMENT AT NIS SHYMKENT - Oxana Shamanova; Aizhan Sarsenbayeva; Bibizada Tukibayeva; Gulzhan Junusbayeva (International Journal of Multidisciplinary Research and Studies, 2023)
In view of the recent developments that have taken place in the realm of technology, it is of the utmost importance for today's educators to be able to facilitate learning that is both effective and efficient through the utilization of various forms of technology in the classroom. This study's objective was to investigate the many kinds of technological tools that biology instructors include in their lesson planning and lecture presentations. In this specific piece of research, the descriptive approach is utilized using observation as well as an interview that is only partially organized. All three of these participants are biology teachers in NIS, Physics, and Mathematics, Shymkent, Kazakhstan are participating in this study. These three educators are now responsible for teaching pupils at the 9th to 12th level in their respective fields of study. The findings of the study were evaluated by applying the technology integration criteria that had been developed by Britten and Casady to the process of putting technology to use in learning and teaching. This evaluation was done by using the technology integration criteria that had been developed by Britten and Casady. Because of this, the findings of the study were able to be represented in a manner that was more accurate. According to the findings of the research, many of the technologies that are used in the biological material of Animalia biology are included in the technology that promotes learning by making use of conventional processes or lectures on the biological material of the Animalia Kingdom. This is the case for most of the technologies that are used in the biological material of Animalia biology. This technology was one of the several technologies that were available. When using technology to teach biology, teachers have several issues that they need to keep in mind. These considerations include the limited facilities, the limited talents of teachers, the tough subject matter, and the learning style that is adopted by pupils. It should come as no surprise that educators in Indonesia require training to improve their capability of incorporating a wide variety of types of technology into the content of the lessons they teach. This is because there are a wide variety of approaches that educators are contemplating adopting in order to integrate technology into their lesson plans.